TINJAUAN PENDEKATAN ETNOMEDIS: PRODUK TANAMAN SEDATIF ALAMI UNTUK PENGOBATAN GANGGUAN KECEMASAN - Dita Sheilla Putri Wahyuningtias; Putu Desy Sagita Ananda; Laurens Frestasya A. Turnip (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Anxiety disorders are common psychiatric conditions associated with significant disability, influenced by a complex interplay of genetic, environmental, and epigenetic factors. Current first-line treatments, including Selective Serotonin Reuptake Inhibitors (SSRIs), Serotonin Norepinephrine Reuptake Inhibitors (SNRIs), and benzodiazepines, remain limited in efficacy and are associated with adverse effects such as addiction, particularly with benzodiazepine use, highlighting the need for novel pharmacological agents derived from natural compounds. Therefore, this review aimed to provide a comprehensive overview of natural compound-based drugs investigated in clinical trials for their potential in treating fear, anxiety, and trauma-related disorders, conducted through a systematic literature search of PubMed, Google Scholar, and Scopus databases using the keywords "natural compound" and "plant for anxiety disorder." The review identified 14 plants with potential benefits for anxiety disorders owing to their sedative properties, among which Kratom (Mitragyna speciosa) demonstrated superior sedative effects compared to benzodiazepine-class benchmark controls, suggesting its promising potential as a novel therapeutic candidate. Nevertheless, further investigation including well-designed clinical trials remains necessary to confirm the safety and efficacy of these natural substances in the management of anxiety disorders.